Challenges on Digital Inclusion: Background, questions, and measurement of the Gender Digital Divide - Zapata, Cristian Berrio; Arraiza, Paloma Marin [UNESP]; Silva, Ester Ferreira da; Soares, Elieth das Chagas (Univ Republica, Fac Psicologia, 2017)
Technological advances applied to information are fast and massive. The consequent changes affect the subject's interaction with the world, demanding a constant technological deconstruction in the basic routines of people. Whoever does not master these cycles is disadvantaged in comparison to those who manage to articulate themselves. Being excluded from Information Technology, in most cases, is a state of constraint derived from economic resources, context infrastructure, information literacy and educational limitations, restrictions of access to labor markets, or sociocultural paradigms. These inequalities create complex divides as their nature is multidimensional, and disarticulate the affected groups from ICT, i.e. women. Such phenomenon has been called Gender Digital Divide (GDD). This article makes a recapitulation on the antecedents of the exclusion of women from the history of computing, the existing problems regarding female entry in engineering and computer engineering careers, and the existence of sexist conditions in the labor market of the computer industry. Then we summarize relevant theoretical models concerning digital gender exclusion and discuss the measurement of GDG, proposing a complementary perspective based on the mapping of imaginaries.
Keywords: Digital Divide; Gender Digital Divide; ICT; Feminism